FREEZE DRYING OF KIWI (ACTINIDIA DELICIOSA) PUREE AND THE POWDER PROPERTIES - Gulsah Calıskan; Kadriye Ergun; S. Nur Dirim (Chiriotti Editori, 2015)
In this study, it was intended to investigate the production of freeze dried kiwi (Actinidia deliciosa) puree in the form of powder that can be used as a natural alternative to synthetic additives used in food products such as pudding, instant tea, and sauces for improving their flavour. In order to obtain the powder product, kiwi puree as plain and with maltodextrin (Dextrose Equivalence of 10-12, as 10 % by weight) addition were freeze dried. Drying behaviour of plain kiwi puree and kiwi puree with MD were explained by Logarithmic model (R2=0.994, RMSE=0.024, χ2=0.0008) and Wang and Singh model (R2=0.999, RMSE=0.012, χ2=0.0002), respectively. The effective moisture diffusivity (Deff) value was calculated as 7.3x10−10 m2/s and it was observed that it was not affected by the addition of MD. The vitamin C content of fresh kiwi fruit was evaluated as 66.3 mg/100 g kiwi and there was a loss of 17.1% for plain and 19.8% for MD containing powders respectively after freeze drying. It was also observed that, the addition of maltodextrin decreased cohesiveness, on the other hand, increased bulk and tapped densities, average time values for wettability and solubility, and glass transition temperature of the powder products.